A new species of Micarea (Pilocarpaceae) from Madeira growing on Usnea. (12th May 2014) - VAN DEN BOOM, Pieter P. G.; ERTZ, Damien
Abstract: The new species Micarea usneae is described from Madeira. It has been found at two localities where it grew on epiphytic Usnea thalli. Micarea usneae is distinguished by a very thin pale brownish thallus, pallid to greyish black or bluish subglobose apothecia of 0·1–0·3 mm diameter, very narrow (1·5–2·5 µm) ascospores, black pycnidia and strongly curved to sigmoid macroconidia. Phylogenetic analyses using mtSSU sequences place the new species in the Micarea peliocarpa group. Catillaria usneicola and Cladonia parasitica are recorded for the first time from Madeira. A key to the lichenicolous species on Usnea in Macaronesia is provided.